Urban renewal after the Berlin Wall - A place-based policy evaluation - Richter Felix; Gabriel Ahlfeldt; Wolfgang Maennig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We use a quasi-experimental research design to study the effects of 22 renewal areas implemented in Berlin, Germany, to increase housing and living quality in the aftermath of the city s division during the Cold War period. Our results suggest within the targeted areas that the policy has helped reduce (increase) the number of buildings in poor (good) condition by 25% (10%). Property prices increased at an annual rate of 0.4-1.8%. However, evidence is weak at best for positive housing externalities. More generally, our findings suggest that estimated place-based policy effects are less sensitive to unobserved local shocks the more treatment and control areas are considered in the analysis.
Keywords: H23; R21; R31; 330